Nakae Chominâ€™s World of Thought and Ideology of the Meiji Period through the â€œGentlemanâ€ Character in â€œA Discourse by Three Drunkards on Government (Sansuijin Keirin Mondo)â€ - Yazici, Yasemin (European Scientific Journal, ESJ, 2024)
From the second half of the 19th century, many intellectuals of the Meiji Japan serve as a referance for us in order to understand the roadmap of Japan which has revealed an important modernization story under the name of the Meiji Restoration. One of the enlightened thinkers we come across at this point is Nakae ChÅmin. Nakae ChÅmin, (1847-1901) contributed to the establishment of concepts such as freedom, equality, democracy and constitutionalism in the political memory of Japan through his articles. At the same time, he created a concept memory in the Japanese political thought and brought new concepts to the Japanese language. In this study, ideology analysis was made in â€œSansuijin Keirin MondÅ (A Discourse by Three Drunkards on Government)â€ which is called Nakae ChÅminâ€™s masterpiece and conveys the ideas of the Meiji period to the reader through different characters. In this work, written with the Socratic dialogue method, the understanding of modernism, idealism, pacifism, freedom, equality, democracy etc. was examined by focusing on the â€œGentlemanâ€, one of the characters described as Nakae ChÅminâ€™s alter ego. At the conclusion of the study, we have determined that a great majority of the ideas put forward by the character of â€œGentlemanâ€ are also included in Nakae ChÅminâ€™s intellectual framework, especially in the liberal views before 1891.